SAT0114 Effects Of Tocilizumab (TCZ) in Combination with Non-Biologic Dmards in the Inhibition of Progression of Synovitis, Bone Marrow Edema and Erosions Evaluated by Extremity-Dedicated Magnetic Resonance Imaging (MRI) In Rheumatoid Arthritis (RA). (23rd January 2014) - Cimmino, M. A.; Sarzi-Puttini, P.; Bombardieri, S.; Iagnocco, A.; Sinigaglia, L.; DeBenedetti, F.
Abstract : Background: Extremity-dedicated MRI is a sensitive method to detect early inflammatory and destructive changes in peripheral joints of RA patients, while reducing costs and decreasing patient's discomfort. Objectives: The objective of this phase IIIb, national, multicentre, open-label study (Eudract n 2009 012185-32) was to assess the effects of TCZ in combination with DMARDs on changes of the synovial membrane enhancement in the wrist joints of RA patients with inadequate response to DMARDs. Methods: TCZ 8mg/kg IV was given every 4 wks for a total of 12 infusions. MRI was performed with a dedicated 0.2T machine (Esaote, Genova, Italy) using pre and post-contrast T1 weighted Turbo 3D, fast T1 weighted Spin Echo in the axial plane, and STIR sequences, at baseline and after 2, 4, 12, 24 and 48 weeks. Changes from baseline to wk 4 in extension and degree of wrist synovitis measured with RA MRI score (RAMRIS) and in quantitative assessment with dynamic, gadolinium-enhanced MRI, were the primary endpoints. Secondary efficacy endpoints were measured up to 48 wks from treatment start. Adverse events (AEs), vital signs and laboratory tests were the safety measures. Results: 58 pts (mean age 51.5 yrs, 78% females, median RA duration 5 yrs) received TCZ (ITT sample) and 8 (13.8%) were discontinued. Mean (±SD) RAMRIS score, but not the dynamic parameters rate of early enhancement (REE) and relative enhancement (RE), significantly decreased from baseline to wk 4 (-0.804±1.575, p=0.018 by Wilcoxon's sign test). Consistent findings were observed in the per-protocol sample (43 pts). In the repeated measures ANOVA model, RAMRIS significantly decreased after only 2 wks and up to wk 48; RE and REE decreased at wk 24 and at wks 12, 24 and 48, respectively. The mean RAMRIS score of bone marrow edema of wrist and metacarpo-phalangeal joints significantly decreased from baseline to wks 24 (-6.70±10.98, p=0.0022) and 48 (-8.30±13.061, p=0.0008), while bone erosion score did not progress. Mean DAS-28 CRP decreased from 5.44±0.90 at baseline to 2.35±1.37 at wk 48. Significant improvement from baseline to wk 48 (p<0.0001) was also observed for the HAQ disability index. Treatment-related AEs were reported in 84.5% of pts but were serious only in one (tachycardia). Hypercholesterolemia and increase of triglycerides were reported in 19% and 14% of pts, respectively. Neutropenia was reported in 14% of pts. There were no important changes from baseline in the other safety parameters. Conclusions: This is the first study evaluating the effect of TCZ in RA patients by contrast-enhanced MRI. TCZ 8mg/kg given in combination with DMARDs in RA pts not responsive to DMARDs therapy was associated with rapid improvements not only of clinical parameters, but also of MRI wrist synovitis and bone marrow edema, with no progression in bone erosions. The safety results were in line with the known profile of TCZ. Disclosure of Interest: None Declared